PENILAIAN IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENJASKES TINGKAT SEKOLAH DASAR NEGERI 4 MEMPAWAH HILIR - Tri Liana (Universitas Tanjungpura, 2020)
AbstractThis study aims to find out:1) Curriculum 2013 implementation, 2) describe the constraints faced in the implementation of the curriculum 2013, 3) the strategy used in the implementation 2013 curriculum in the orchestra education in public elementary school 4 Mempawah. This study is an evaluation research using the CIPP (Contex, Input, Process and Product) developed by Stufflebeam. Data was obtained through curriculum expert validation questionnaires, observation and interviews. Data analysis was carried out qualitative. The results of the study show that: 1) the implementation of the Curriculum 2013 has largely gone smoothly, from 4 schools incorporated only 1 school has not fully planned the implementation of Curriculum 2013, due to the lack of socialization and assistance to teacher and the lack of available facilities at school, 2) the obstacles faced in the implementation of the Curriculum 2013 were the lamitations of orchestra teacher and the limited of infrastructure to support practical activities and the lack of supporting books, library and internet network. 3) the strategy to overcome the obctacles in the implementation of curriculum 2013 that needs to be prepared furthur is to make good planning based on needs analysis and the existence of good synergies between the central goverment and the provincial as well as local government. There are still many confusions, this is due to the large number of assesment components that must be carried out as demands of the Curriculum 2013. Keywords: Assesment Implementation of the Curriculum 2013, Physical Education